Abbreviation of larval development and extension of brood care as key features of the evolution of freshwater Decapoda - Vogt, Günter (Biological reviews, 2013)
The transition from marine to freshwater habitats is one of the major steps in the evolution of life. In the decapod crustaceans, four groups have colonized fresh water at different geological times since the Triassic, the freshwater shrimps, freshwater crayfish, freshwater crabs and freshwater anomurans. Some families have even colonized terrestrial habitats via the freshwater route or directly via the sea shore. Since none of these taxa has ever reinvaded its environment of origin the Decapoda appear particularly suitable to investigate life-history adaptations to fresh water. Evolutionary comparison of marine, freshwater and terrestrial decapods suggests that the reduction of egg number, abbreviation of larval development, extension of brood care and lecithotrophy of the first posthatching life stages are key adaptations to fresh water. Marine decapods usually have high numbers of small eggs and develop through a prolonged planktonic larval cycle, whereas the production of small numbers of large eggs, direct development and extended brood care until the juvenile stage is the rule in freshwater crayfish, primary freshwater crabs and aeglid anomurans. The amphidromous freshwater shrimp and freshwater crab species and all terrestrial decapods that invaded land via the sea shore have retained ocean-type planktonic development. Abbreviation of larval development and extension of brood care are interpreted as adaptations to the particularly strong variations of hydrodynamic parameters, physico-chemical factors and phytoplankton availability in freshwater habitats. These life-history changes increase fitness of the offspring and are obviously favoured by natural selection, explaining their multiple origins in fresh water. There is no evidence for their early evolution in the marine ancestors of the extant freshwater groups and a preadaptive role for the conquest of fresh water. The costs of the shift from relative r- to K-strategy in freshwater decapods are traded-off against fecundity, future reproduction and growth of females and perhaps against size of species but not against longevity of species. Direct development and extension of brood care is associated with the reduction of dispersal and gene flow among populations, which may explain the high degree of speciation and endemism in directly developing freshwater decapods. Direct development and extended brood care also favour the evolution of social systems, which in freshwater decapods range from simple subsocial organization to eusociality. Hermaphroditism and parthenogenesis, which have evolved in some terrestrial crayfish burrowers and invasive open water crayfish, respectively, may enable populations to adapt to restrictive or new environments by spatio-temporal alteration of their socio-ecological characteristics. Under conditions of rapid habitat loss, environmental pollution and global warming, the reduced dispersal ability of direct developers may turn into a severe disadvantage, posing a higher threat of extinction to freshwater crayfish, primary freshwater crabs, aeglids and landlocked freshwater shrimps as compared to amphidromous freshwater shrimps and secondary freshwater crabs.
First published: 14 August 2012
Gesehen am 08.10.2018